Estimating tissue-specific peptide abundance from public RNA-Seq data - Frentzen, Angela; Greenbaum, Jason A.; Kim, Haeuk; Peters, Bjoern; Koşaloğlu-Yalçın, Zeynep (Frontiers in Genetics, 2023)
Several novel MHC class I epitope prediction tools additionally incorporate the abundance levels of the peptides’ source antigens and have shown improved performance for predicting immunogenicity. Such tools require the user to input the MHC alleles and peptide sequences of interest, as well as the abundance levels of the peptides’ source proteins. However, such expression data is often not directly available to users, and retrieving the expression level of a peptide’s source antigen from public databases is not trivial. We have developed the Peptide eXpression annotator (pepX), which takes a peptide as input, identifies from which proteins the peptide can be derived, and returns an estimate of the expression level of those source proteins from selected public databases. We have also investigated how the abundance level of a peptide can be best estimated in cases when it can originate from multiple transcripts and proteins and found that summing up transcript-level expression values performs best in distinguishing ligands from decoy peptides.